Hubungan Antara Kecerdasan Linguistik Dengan Hasil Belajar Ilmu Pengetahuan Alam Siswa SD Laboratorium UNESA - Aini, Dewi Nurul (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study is a correlational study, which aims to determine the relationship between linguistic students with the learning outcomes of Natural Sciences ( IPA ). The population in this study are all elementary students UNESA Laboratory. Meanwhile, the sample is the entire fifth-grade elementary school students UNESA Laboratory totaling 80 students. Data were collected by using linguistic intelligence tests and documentation of learning outcomes Natural Sciences ( IPA). Linguistic intelligence test consisting of 14 items were sourced from the internet. While documentation of science learning outcomes derived from the average value of test scores 4 times daily. Daily tests developed and implemented by the teacher concerned. The data analysis technique used is the product-moment correlation statistical techniques with calculations using SPSS version 20. These results indicate that there is a relationship between linguistic intelligence with the Natural Sciences learning outcomes with value (rxy) of 0, 578 were classified as a medium category.